The Acceptance of Relevant Market in Moroccan and European Competition Law: Origins and Evolution - Mohamed El Azhary (European Scientific Journal, ESJ, 2025)
The assessment of barriers to market access requires, first and foremost, the implementation of an approach that views any infringement of equal opportunities between firms as a restriction on free competition. Such an approach, which is likely to contribute to preserving equality in competition and even encouraging dynamic competition between market players, remains dependent on the interest shown in the legal implementation of the definition of the relevant market itself. This research aims to establish a conceptualization of the legal criteria that promote the organization of competitive inflows within the market. In pursuing this goal, we will draw upon the definition of the relevant market according to Moroccan and European legal standards, which are the subjects of our research. Consequently, in order to reach this target, it is imperative to focus on a totalizing approach, enabling us to grasp the origins of the relevant market, to gauge and foresee its implementation, especially in accordance with economic thought and law.